Efeitos do treinamento funcional na aptidão física de mulheres idosas da Universidade da Maturidade do Amapá - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
Objective: To investigate the effects of functional training in physical fitness of elderly women in the city of Macapá-AP. Methods: The sample included 27 women regularly enrolled in the project Universidade da Maturidade do Amapá (UMAP), older than or equal to 60 years, sedentary and independent in performing instrumental activities of daily living. The volunteers underwent a functional training program, performed three times a week during three months. At the end of every month of intervention, the volunteers were evaluated through a battery of Rikli & Jones tests, as well as on the 30th day after the end of the program. Results: After twelve weeks of functional training older showed an increase of 113% (p <0.01) in muscle strength of the lower limbs, 95.16% (p <0.01) in muscle strength of upper limbs, 315.2% (p <0.01) in the flexibility of lower limbs, 99.2% (p <0.05) in the flexibility of upper limbs; 34.4% (p <0.01) mobility, and 191.8% (p <0.01) in aerobic capacity. However, there was no significant changes in body composition (p = 0.72). After a period of four weeks of detraining, the elderly showed a significant decline in skills, particularly: flexibility of upper limbs (245.16% (p <0.01) and mobility 18.37% (p <0.0001), no showing significant changes in body composition (0.28%, p <0.72). Final thoughts: A three month training program has been shown to change significantly positively skills of physical fitness of the elderly, such as flexibility of upper and lower limbs, aerobic capacity, muscle strength of upper and lower limbs, and mobility, which can reduce the aging of the negative repercussions on the independence of the elderly. However a 4 week period was sufficient to cause significant decreases in gains made on TF program, particularly in flexibility of the upper limbs
Keywords: Treinamento funcional; Exercícios físicos para idosos; Aptidão física; Idosos - Saúde e higiene; CNPQ::CIENCIAS DA SAUDE::EDUCACAO FISICA; CNPQ::CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA; PROCEDIMENTOS E ATENÇÃO EM SAÚDE NO TRÓPICO ÚMIDO DA AMAZÔNIA; EPIDEMIOLOGIA E SAÚDE PÚBLICA